2021
DOI: 10.3389/fenrg.2021.771433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping in Electricity Demand Forecasting: A Scientometric Insight

Abstract: Electricity demand forecasting plays a fundamental role in the operation and planning procedures of power systems, and the publications related to electricity demand forecasting have attracted more and more attention in the past few years. To have a better understanding of the knowledge structure in the field of electricity demand forecasting, we applied scientometric methods to analyze the current state and the emerging trends based on the 831 publications from the Web of Science Core Collection during the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Muhammad Zubair et al (2011) [11] presented a method for reliability parameters calculation and their updating in Probabilistic Safety Assessment. Dingqing Guo et al (2021) [12] presented a method for dynamic reliability evaluation of diesel generator system.…”
Section: Introductionmentioning
confidence: 99%
“…Muhammad Zubair et al (2011) [11] presented a method for reliability parameters calculation and their updating in Probabilistic Safety Assessment. Dingqing Guo et al (2021) [12] presented a method for dynamic reliability evaluation of diesel generator system.…”
Section: Introductionmentioning
confidence: 99%
“…Electricity demand forecasting becomes increasingly important (Yang et al, 2021) and distinguishing between different households in electricity consumption leads to more accurate results (Grandjean et al, 2012;Carlson et al, 2013). Tusting et al (2019) showed correlations between housing type and socio-economic factors by analyzing 51 national census reports in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Investigate the factors that have a significant effect on the electricity consumption in residential sectors. (3) Apply modern data science approaches, namely the seasonal statistical method (SARIMAX) and the machine learning algorithm (NARX), to forecast short-term electricity demand. (4) Find the best model by automatic tunning hyperparameters via the Bayesian optimization algorithm (BOA).…”
Section: Introductionmentioning
confidence: 99%